Lloyd's maritime atlas of world ports and shipping places (Informa Law from Routledge, 2016)
A comprehensive way to locate the world's ports and shipping places. It includes: expanded maps of East Africa, the Red Sea, Japan and Malaysia; World Distance Tables; and, statistics on the top ports, flags, shipowner countries and types of ships